2020
DOI: 10.1111/aos.14576
|View full text |Cite
|
Sign up to set email alerts
|

Laser trabeculoplasty in newly diagnosed multi‐treated glaucoma patients

Abstract: To evaluate the intraocular pressure (IOP)-lowering effect of laser trabeculoplasty (LTP) in eyes which IOP had been substantially reduced by intensive topical treatment for one week. Methods: Patients with newly diagnosed open-angle glaucoma were randomized to treatment with three IOP-lowering substances. One week later, 360°argon or selective LTP was performed. IOP was measured before LTP and at one-, three-, six-and 12-month post-LTP. The patients were part of the Glaucoma Intensive Treatment Study (GITS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
5
1
Order By: Relevance
“…The only factor that was identified as being associated with a higher treatment failure was a lower baseline IOP. This is consistent with previous studies that show that patients with a higher baseline IOP have better IOP lowering outcomes after SLT [21][22] . At least one previous study demonstrated that fewer laser spots was associated with high treatment failure [14] .…”
Section: Discussionsupporting
confidence: 93%
“…The only factor that was identified as being associated with a higher treatment failure was a lower baseline IOP. This is consistent with previous studies that show that patients with a higher baseline IOP have better IOP lowering outcomes after SLT [21][22] . At least one previous study demonstrated that fewer laser spots was associated with high treatment failure [14] .…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, there was no difference in LTP effect between eyes with POAG or PEXG, neither at 12 (Rasmuson et al, 2021) nor the 60-month follow-up visits. This was unexpected since patients with PEXG often have highly pigmented trabecular meshwork.…”
Section: Follow-upcontrasting
confidence: 73%
“…That report included a linear regression analysis defining the correlation between pre‐LTP IOP and the IOP reduction after laser treatment. It showed that LTP was beneficial in multi‐treated eyes if the IOP before laser was ≥15 mmHg and that the effect was maintained up to 1 year, but this was not true for eyes with IOP lower than 15 mmHg (Rasmuson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, according to what was proven many times,3,24 a higher preoperative mdIOP was not a predictor for success in the cohort studied as was shown with regression and correlation analysis. We hypothesize, that prostaglandins, which are common mediators in the inflammatory response caused by SLT might enhance uveoscleral outflow in such a way that the pressure gradient is not the driving force.…”
Section: Discussionmentioning
confidence: 58%